Dynamic Removal of Toxic Metals from Wastewater using Perlite as Sorbent - Munaf, Edison; Suhaili, Refilda; Anwar, Yefrida; Zein, Rahmiana (Asian Journal of Chemistry, 2010)
Expanded perlite has been used as an adsorbent for the effective removal of chromium, cadmium, copper and zinc from laboratory wastewater. The percent removal of toxic metals investigated at pH 6 were in the range of 75-90 % for Cr(III), Cu(II) and Zn(II). While Cd(II) could be remove from aqueous solution around 75 % at pH 7-8. Diverse metal ions, i.e. Cr(III), Zn(II) and Cd(II) could significantly reduce the Cu removal at concentration ratio 1:4 for Cu:Cr, 1:6 for Cu:Zn and Cu:Cd. Sorption capacities are 29.7, 23.5, 27.3 and 24.7 mg/g perlite for Cr(III), Zn(II), Cu(II) and Cd(II), respectively. Desorption of metal ions from adsorbent were in the range of 83-99 % at pH 1. All the metal ions concentration was measured using atomic absorption spectrophotometric detection. Application of the proposed method was successfully demonstrated using the laboratory wastewater.